2010
DOI: 10.1126/science.1186992
|View full text |Cite
|
Sign up to set email alerts
|

Physical Phenomena in Real Time

Abstract: The use of videos allows teachers to tame the vagaries of experimentation while engaging students in the process of physics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 1 publication
0
7
0
2
Order By: Relevance
“…Remote laboratories, such as in Nickerson et al [17], generate authentic data for students to analyze, interpret, and draw conclusions from. In addition to simulations and remote laboratories, video clips were chosen by Brookes and Etkina [33]. Users can download and analyze the videos through QuickTime.…”
Section: B Technology Support For the Openness Of Laboratory Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote laboratories, such as in Nickerson et al [17], generate authentic data for students to analyze, interpret, and draw conclusions from. In addition to simulations and remote laboratories, video clips were chosen by Brookes and Etkina [33]. Users can download and analyze the videos through QuickTime.…”
Section: B Technology Support For the Openness Of Laboratory Activitiesmentioning
confidence: 99%
“…Empirical studies have shown that this feature improves students' graph interpretation and modeling [34,35]. Specifically, Etkina and colleagues foster students' ability of explanation by asking them to make predictions based on experiments they observe online [33]. Students can repeat various experiments online in a short period of time to accumulate enough data.…”
Section: B Technology Support For the Openness Of Laboratory Activitiesmentioning
confidence: 99%
“…Third, it may be that the Investigative Science Learning Environment (ISLE) provides a perspective on pedagogy that addresses the observed gap between the performance of blue and green students [44]. We will be explicitly modifying the activities we use for collaborative learning to incorporate the rubrics developed by ISLE.…”
Section: Discussionmentioning
confidence: 99%
“…The process is iterative and cyclical, "at any step, one can go back and revisit the previous step or examine the assumptions [26]." "The goal is to engage students in actions and decisions similar to those of real physicists by working with simple experiments [27]." The ISLE method has been shown to help students design experiments, analyze data, and communicate like scientists [12,28,29].…”
Section: A Review Of the Literature On Student-analyzed Videomentioning
confidence: 99%